Pembelajaran Alternatif Berbasis Proyek Kreatif Rumah pada Masa Pandemi Covid-19 - Wardiani, Ririn; Wulandari, Rifa Suci; Astuti, Cutiana Windri; Novitasari, Lusy (Jurnal PGSD, 2021)
This research aims to describe alternative home based learning activities, home used as learning source. That learning alternative is derived from the concept of Multiple Intelligences development, Home as Finnish learning setting education and emergency curriculum proposed by Kemendikbud. The method used is library analysis. The discussion about this learning alternative focuses on kinesthetic intelligence so that it can be done easily by parents. The form of learning alternative is creative project involves My creation, My sport,  a Dancer, Traditional Games, Outbound, Fun Cooking, Gardening. That creative project is valued academic activities based on Basic Competence stated in curriculum. Teaching and learning process in Elementary level mainly focuses on thematic integrative  learning. The proposed learning alternative can facilitate the students to reach the essential basic competence recomended by the school. In this case, learning alternative is correlated with literacy competence, numeric, character education, and life skill.